Legal Position of Muhakkam Guardians in the Practice of Sirri Marriage in Aceh - Pakpahan, Emir Syarif Fatahillah; Amalia, Reni; Muhammaddiah, Muhammad Rusdi bin; Rizal, Said (Hukum Keluarga Islam IAIN LANGSA, 2024)
The position of the guardian in marriage is the most important thing in marriage. Because its existence is the reason for the validity of a marriage. The guardians consist of the nasab guardian, the judge guardian (sultan), the muhakkam guardian, and the maula guardian. This research examines the dynamics of unregistered marriages in East Aceh Regency, which are related to who is the guardian in the marriage. How does the muhakkam guardian handle unregistered marriages? What is the legal position of muhakkam guardians as guardians of unregistered marriages? This research aims to answer the problems of muhakkam guardians. This research uses empirical legal methods with a field study approach. Data was obtained by collecting information from primary sources through interviews. The results of the research explain that: first, siri marriage through muhakkam guardians using a cultural approach and Islamic legal studies. Second, the legal position of muhakkam guardians is not regulated in Indonesian legislation, so it cannot be used as a legal basis for carrying out unregistered marriages. Muhakkam guardians tend to be used to legalize sirri marriages, which are very common among the people of East Aceh. Even though it is not recognized by the state, in practice, muhakkam guardians have religious legal power. Sociologically, the presence of muhakkam guardians increases the number of unregistered marriages among the people of East Aceh